2005
DOI: 10.1007/s00018-005-5024-4
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester up-regulates aldose reductase expression in A549 cells: a potential role for aldose reductase in cell cycle modulation

Abstract: Over-expression of aldose reductase (AR) has been observed in many cancer cells. To clarify the role of AR in tumor cells, we investigated the pathways mediating expression of the AR gene induced by 12-O-tetradecanoylphorbol-13-acetate (TPA), a potent tumor promoter. In A549 human lung adenocarcinoma cells, TPA elicited a dose- and time-dependent increase in AR mRNA level with an elevated enzyme activity. The TPA-induced increase in mRNA level and promoter activity of the AR gene was significantly attenuated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
2
6
0
1
Order By: Relevance
“…4). Our results showing the arrest of Caco-2 cells at S phase by AR inhibition are similar to human lung adenocarcinoma cells (43).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…4). Our results showing the arrest of Caco-2 cells at S phase by AR inhibition are similar to human lung adenocarcinoma cells (43).…”
Section: Discussionsupporting
confidence: 83%
“…These observations suggest that AR is a growth-responsive protein, which may be involved in facilitating metabolic changes that accompany growth of colon cancer cells. Consistent with this view, other investigators (23,40,42,43) have shown that the expression of AR is minimal in quiescent cells and is robust under hyperglycemic and growth factor-induced oxidative stress. Prevention of growth factor-induced PGE 2 production and cell growth by pharmacologic inhibition of AR by sorbinil was further confirmed by ablation of AR (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Because sorbitol and myo-inositol are structurally similar, the depletion of myo-inositol appears to be due in part to the inhibition of its uptake in cells accumulating sorbitol [87]. Furthermore, it has recently been demonstrated that stimulation of PKC by phorbol esters up-regulates AKR1B1 indicating that some of the injurious effects of PKC activation may be mediated by AKR1B1 [88]. Accumulating evidence suggests that effects of non-enzymatic glycosylation and AKR1B1 are inter-related [89,90].…”
Section: Akr1b1 In the Pathophysiology Of Inflammatory Disordersmentioning
confidence: 99%
“…TPA has been reported to promote cell proliferation and cell cycle progression in A549 cells (22). COX-2 is associated with cell proliferation and growth in some cancerous conditions (23), and the inhibitors of COX-2 are able to interfere cell cycle progression by regulating the cell cycle -related proteins, such as cyclins (24), which are critical for oncogenic transformation (21).…”
Section: Cox-2 Regulated Tpa-induced Cell Cycle Progressionmentioning
confidence: 99%